Systematic review of hospital-wide complication registries - Saarinen I; Malmivaara A; Miikki R; Kaipia A (JOHN WILEY & SONS LTD, 2022)
Background: An institutional registry covering all surgical specialties could be an implementation tool in quality benchmarking between hospitals and aid determination of their cost-effectiveness. The objective of this systematic literature review was to evaluate original articles on existing prospective surgical registries that can be used by single institutions across surgical specialties.Method: A systematic review of the literature using PRISMA guidelines was conducted for articles focusing on hospital-wide surgical registries. Single-specialty retrospective registries, non-defined outcome measures or system protocols, and studies not in English were excluded.Results: Five articles were included for analysis. Evaluation of the articles revealed wide methodological heterogeneity in the classification and categorization of complications and data collection methods.Conclusion: Ideal surgical quality monitoring systems should be real-time, contain patient-related risk factors, and encompass all surgical specialties. At present, such institutional registries are rarely reported and no consensus exists on their standard definitions and methodology.